Implementation of Public-Private Partnership Model Towards Ideal Operationalization of Correctional Institution in Indonesia - Aisyah, Sani Siti, - (Jurnal Kriminologi Indonesia, 2025)
The increasing popularity of Public-Private Partnership (PPP) in prison or correctional institution development and management is currently often studied from an economic perspective that prioritizes state budget efficiency and is rarely studied from a social perspective that prioritizes benefits for the community in the context of social control. Realizing that PPP has positive potential in the ideal operationalization of correctional institution amidst limited human resources and budget, this study examines various correctional institution PPP models using the correction theory framework. This study was designed as an exploratory qualitative study using interview, document studies, field observations and FGD. This study successfully identified 5 correctional institution PPP models, namely: 1) "private governance"; 2) "hybrid management"; 3) "limited hybrid management"; 4) "service infrastructure"; and 5) "contracting out certain limited functions". The correctional institution PPP model that has the potential to create safe, humane and productive correctional institution conditions is the model that does not allow private involvement in correctional institution administration and management as well as in the custody aspect of correction services. The determinant factors that must be considered in determining and implementing those correctional institution PPP models are: 1) ideology and constitution; 2) goals or philosophy of correction; 3) needs; and 4) budget. In Indonesia, the “limited hybrid management” model is suitable for the operationalization of industry in medium and minimum security correctional institution to provide inmates with work skills.